Thermal And Flow Analysis Of Piezoelectric Fans For Cooling LEDS Packages - Shaker , Sufian Farid (2014)

(untitled)
Computers, LED packages and portable electronic devices, such as minilaptops, tablets, and cellular phones, are rapidly emerging in lighter, slimmer, and more compact forms with high functionalities to meet consumer demands. This tremendous growth in advance electronics necessitates modern solutions to be adapted with the new challenges of thermal management. One of the recent thermal solutions is piezoelectric fans, which recently considered as a very strong candidate for cooling the next generation in general microelectronic devices. Komputer, pakej LED dan alatan elektronik mudah-alih, seperti komputer riba mini, tablet, telefon sel, meningkat dengan ketara dari segi bentuk, ringan, nipis, dan lebih padat dengan fungsi yang tinggi bagi memenuhi permintaan pelangan. Pertumbuhan yang ketara ini dalam elektronik termaju memerlukan penyelesaian moden bagi menyesuaikan dengan cabaran baru pengurusan terma. Salah satu daripada penyelesaian terma terbaru adalah kipas piezoelektrik, yang mana baru-baru ini dianggap sebagai alat yang amat sesuai bagi penyejukan generasi hadapan dalam alatan mikroelektronik umum.